Effect of heavy strength training on classical indicators of endurance cycling performance - Ronnestad, B.; Hansen, E. A.; Raastad, T. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Training is the first and most obvious way to improve cycling performance (2). Incorporation of strength training in cyclists` preparation has previously received some attention (1), and it has been shown that strength training may improve lactate threshold and cycling performance in untrained subjects (3). However, the effect of adding heavy strength training to usual endurance training in well-trained cyclists on endurance cycling performance indicators has not been thoroughly studied. Thus, the aim was to test the hypothesis that heavy strength training improves classical indicators of endurance cycling performance. Twenty well-trained cyclists were assigned to either usual endurance training combined with heavy strength training [E+S; n=11 (♂=11), 27±2 years, 75±3 kg, VO2max 66.8±1.6 ml∙kg-1∙min-1] or to usual endurance training only [E; n=9 (♂=7, ♀=2), 30±2 years, 74±3 kg, VO2max 65.9± 2.0 ml∙kg-1∙min-1]. The strength training consisted of four lower body exercises (half squat, leg press with one foot at a time, one-legged hip flexion, and toe raise, 3x4-10RM), which were performed twice a week for 12 weeks. Pre- and post-tests determined the cyclists` thigh muscle cross-sectional area (CSA), maximal voluntary contraction force (MVC) in isometric half squat, peak power output during a 30 s Wingate test, power output at 2 mmol blood lactate concentration during an incremental cycling test, VO2max, and mean power output during a 40-min all out cycling trial. Data are presented as mean±SE. At baseline, the groups were similar. After the intervention period, E+S increased CSA of thigh muscles (4.5±0.6%), MVC (21.2±4.9%), peak power output in the 30 s Wingate test (9.5±2.9%), and power output at 2 mmol blood lactate concentration (4.1±1.5%). These variables were not changed in E. There was a significant difference between groups in relative improvement in MVC half squat, CSA of the thigh muscles, and peak power output. Both E+S and E increased their VO2max (3±1% and 6±2%, respectively) with no statistical difference between groups. E+S increased their mean power output during 40-min all out cycling while there was a tendency for a similar finding in E (p=0.054). The overall finding was that adding heavy strength training to usual endurance cycling training results in favourable adaptations in classical performance indicators without compromising the development of VO2max. In contrast, adding explosive strength training to trained cyclists has been reported not to affect cycling performance and cycling economy (1). It is possible that the discrepancy is due to the difference between strength training regimens. In conclusion, adding heavy strength training to usual endurance training improves classical indicators that routinely are used to evaluate and predict endurance cycling performance.